Factors Influencing Students' Career Maturity in Vocational and General High School - Gita Aulia Nurani (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2022)
Career maturity is a continual process of development that demonstrates notably recognised attributes required for career advancement. However, internal and environmental variables determine career maturity. This study explores the aspects of career maturity in high school students by collecting the literature. The following criteria were used to choose articles for inclusion: 1) articles describing career maturity in general high school or vocational high school; 2) articles published in English or Indonesian; 3) entire passages in published works; 4) published during the previous ten years. Results mentioned students at vocational high schools typically have more components than students in general high schools. Social attachment, adversity intelligence, emotional intelligence, career interest, motivation, and career aspirations are maturity elements that show in vocational students. Meanwhile, self-determination, self-esteem, self-actualisation, self-confidence, and psychological well-being, on the other hand, are characteristics that impact the professional maturity of general high school students. Since most of these elements are internal to students, it is critical for general high school students to recognise self-reinforcement and self-understanding.